A Catábase e o Sagrado no romance Ângelo Sobral desce aos infernos - Ciuffa, Ana Cristina Zago de Mesquita (2020)
This paper investigates the narrator catabases Ângelo Sobral of the work Ângelo Sobral desce aos infernos, from Ruy Espinheira Filho. It aims, from the experiences of the characters, to unravel the process of recognition of the sacred in individuals, using as its main tool catabase, which can be experienced by all, since it´s a natural process belonging to the confrontation of the individual with himself, which it is from the field of the sacred. The theme of catabase is still shyly researched in dissertations and theses, as well as this work under analysis. It is considered an ancestral theme, religious by excellence, which in mythology includes the descent into the infernal worlds (Hades), undertaken by many characters such as Orpheus, Ulysses, Aeneas and Dante, all followed by anabase (ascent), return of a more complete person. It is also called by catabase the "descent" to the unconscious not yet unraveled, not yet accepted, not recognized, the shadow side of individuals as Jungian nomination. We will use the theoretical support of Carl Gustav Jung, Rudolf Otto, Joseph Campbell, Mircea Eliade, Junito Brandao among others, in a literary study that also encamp psychology and religion.